The systemic effect of PEG-nGO-induced oxidative stress in vivo in a rodent model - Ain, Qura Tul; Haq, Samina Hyder; Alshammari, Abeer; Al-Mutlaq, Moudhi Abdullah; Anjum, Muhammad Naeem (Beilstein journal of nanotechnology, 2019)
Oxidative stress (OS) plays an important role in the pathology of certain human diseases. Scientists have developed great interest regarding the determination of oxidative stress caused after the administration of nano-graphene composites (PEG-nGO). Graphene oxide sheets (GOS) were synthesized via a modified Hummer's method and were characterized by X-ray diffraction (XRD), ultraviolet–visible spectroscopy (UV), and transmission electron microscopy (TEM). The method of Zhang was adopted for cracking of GOS. Then nano-graphene oxide was PEGylated with polyethylene glycol (PEG). PEGylation of nGO was confirmed by Fourier-transform infrared spectroscopy (FTIR), UV spectroscopy and TEM. The average size distribution of nGO and PEG-nGO was determined by using dynamic light scattering (DLS). Subsequently, an in vivo study measuring a marker for oxidative stress, namely lipid peroxides, as well as antioxidant agents, including catalase, superoxide dismutase, glutathione, and glutathione S-transferase was conducted. A comparison at different intervals of time after the administration of a dose (5 mg/kg) of PEG-nGO was carried out. An increase in free radicals and a decrease in free radical scavenging enzymes in organs were observed. Our results indicated that the treatment with PEG-nGO caused an increased OS to the organs in the first few hours of treatment. However, the liver completely recovered from the OS after 4 h. Brain, heart and kidneys showed an increased OS even after 4 h. In conclusion increased OS induced by PEG-nGO could be detrimental to brain, heart and kidneys.